Implementation and Impact of RMI : A Survey of Stakeholders in Seven Member Countries - Pinard, M.I.; Kaombwe, S.M.A. (World Bank, Washington, DC, 2014)
Following extensive consultations with both public and private sector stakeholders, the Road Management Initiative (RMI) formerly known as Road Maintenance Initiative was launched in the late 1980.s as a component of the Sub-Saharan Africa Transport Policy Program (SSATP). This program was led by the Africa Region Infrastructure Department of the World Bank and the Economic Commission for Africa (UNECA) in response to an increasing concern over deteriorating road infrastructure in Sub-Saharan Africa (SSA) despite substantial capital investments by governments and donors. Since its inception, the RMI has focused its activities on finding ways and means of reversing the process of decline that was trapping SSA governments in the cycle of road building, roads collapsing prematurely and roads being rebuilt long before the end of their design life. These activities have generally been pursued within the context of a key concept to emerge from the RMI program. that of commercialization of the roads sector, i.e. bringing roads into the market place, charging for their use on a fee-for-service basis and managing them like any other business. At the 14th RMI Annual Coordinating Committee Meeting (CCM) held in Pretoria, South Africa in December 1999, member states recommended the commissioning of a survey in selected countries to obtain stakeholders views on the RMI vision and strategy and on what changes seem necessary in the RMI approach to more effectively facilitate implementation of sustainable reforms. The survey was undertaken in seven countries: Ghana, Kenya, Malawi, Tanzania, Uganda, Zambia and Zimbabwe and the key issues addressed were: 1) Stakeholders perceptions of the RMI vision for sustainable road management; 2) The barriers, constraints and concerns hampering attainment of the RMI vision; 3) The need for change in the RMI approach, focus and resources; and 4) Indicators to be used to monitor progress in the implementation and impact of reforms. This paper reports on the survey's outcome.